Consumer engagement and the practice of Small and Medium Enterprises (SMEs) in social media / Norhaniza Md Akhir … [et al.] - Md Akhir, Norhaniza; Amirnordin, Nur Alia; Abd Karim, Hilwana; Maknu, Tengku Sharifeleani Ratul; Ramli, Zarifah Fadilah; Haron, Hazliza (2018)
The term “engagement” is now receiving increasing attention among academicians and business practitioners across all industries including small and medium industries. However, the limited number of research leaves room for further exploration and understanding the nature and scope of consumer engagement. Drawing on literature analysis, this study provides marketing academics and practitioners’ insights into the consumer engagement concepts. The study reviews how the small and medium enterprises (SMEs) can generate business value from the use of social media. This study first identifies the key issues involved in the social media practice. It then explores the theoretical foundations of consumer engagement in the academic literatures and in specific business practice applications. The analysis found that social media plays an important role in the process of consumer engagement, which later contribute to the business value and able to generate benefits to the SMEs. The findings of the study will facilitate further understanding on the consumer engagement and the benefits resulting from the social media practice by small and medium enterprises (SMEs). The paper concludes with a discussion of implications for practice and further research.